Genetic Variants in Diseases of the Extrapyramidal System - Oczkowska, Anna; Kozubski, Wojciech; Lianeri, Margarita; Dorszewska, Jolanta (Current Genomics, 2014)
Knowledge on the genetics of movement disorders has advanced significantly in recent years. It is now recognized that disorders of the basal ganglia have genetic basis and it is suggested that molecular genetic data will provide clues to the pathophysiology of normal and abnormal motor control. Progress in molecular genetic studies, leading to the detection of genetic mutations and loci, has contributed to the understanding of mechanisms of neurodegeneration and has helped clarify the pathogenesis of some neurodegenerative diseases. Molecular studies have also found application in the diagnosis of neurodegenerative diseases, increasing the range of genetic counseling and enabling a more accurate diagnosis. It seems that understanding pathogenic processes and the significant role of genetics has led to many experiments that may in the future will result in more effective treatment of such diseases as Parkinson’s or Huntington’s. Currently used molecular diagnostics based on DNA analysis can identify 9 neurodegenerative diseases, including spinal cerebellar ataxia inherited in an autosomal dominant manner, dentate-rubro-pallido-luysian atrophy, Friedreich’s disease, ataxia with oculomotorapraxia, Huntington's disease, dystonia type 1, Wilson’s disease, and some cases of Parkinson's disease.
Keywords: Wilson’s disease